2015
DOI: 10.1155/2015/670724
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Emotion Regulation: Exploring the Neurocognitive Mechanisms behind Mindfulness

Abstract: The purpose of this paper is to review some of the psychological and neural mechanisms behind mindfulness practice in order to explore the unique factors that account for its positive impact on emotional regulation and health. After reviewing the mechanisms of mindfulness and its effects on clinical populations we will consider how the practice of mindfulness contributes to the regulation of emotions. We argue that mindfulness has achieved effective outcomes in the treatment of anxiety, depression, and other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 72 publications
4
94
0
3
Order By: Relevance
“…The increase in levels of psychological well‐being in the participants of the experimental group supports the positive impact of mindfulness on the mental health of people who have participated in other studies on its effectiveness (Grecucci et al, ). Clearer thinking and better internal and external relations (Moscoso & Lengacher, ) will generate more positive behaviors or lifestyles (Cepeda‐Hernández, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increase in levels of psychological well‐being in the participants of the experimental group supports the positive impact of mindfulness on the mental health of people who have participated in other studies on its effectiveness (Grecucci et al, ). Clearer thinking and better internal and external relations (Moscoso & Lengacher, ) will generate more positive behaviors or lifestyles (Cepeda‐Hernández, ).…”
Section: Discussionsupporting
confidence: 78%
“…In recent years, research on mindfulness has focused on this type of intervention's mechanisms of action (Campos, Cebolla, & Mira, ; Grecucci, Pappaianni, Siugzdaite, Theuninck, & Job, ). Results have suggested that mindfulness acts directly on erroneous cognitive processes, so that trained participants experience less cognitive rumination (Paul, Stanton, Greeson, Smoski, & Wang, ) and better emotional regulation (Compare, Zarbo, Shonin, Van Gordon, & Marconi, ), which makes them less vulnerable to developing depressive symptoms or presenting a relapse (Barnhofer et al, ).…”
mentioning
confidence: 99%
“…Results broadly suggest that MM reduces pain, decreases anxiety and depression, and promotes well‐being (Eberth & Sedlmeier, ; Marchand, ). A number of mechanisms have been proposed to elucidate how MM promotes health and well‐being, with stress (Creswell & Lindsay, ), emotion regulation (Grecucci, Pappaianni, Siugzdaite, Theuninck, & Job, ), negative emotion (NE; Sedlmeier et al., ), and positive emotion (PE; Garland et al., ) all identified as potential pathways. However, there are theoretical inconsistencies in the literature regarding associations between MM and PE; some theories suggest that MM should promote PE whereas others suggest that MM should attenuate high‐arousal emotions regardless of whether they are positive or negative in valence (Garland et al., ; Goyal et al., ; Kabat‐Zinn, ).…”
Section: Introductionmentioning
confidence: 99%
“…Practicing them enables a person to witness his/her own sensations, emotions and thoughts without judgment, which can help to acknowledge and accept as it is across daily life (Grecucci, Pappaianni, Siugzdaite, Theuninck, & Job, 2015), gaining awareness and insight toward the relief of suffering and greater happiness (Schmidt, 2004), yet with openness, curiosity, and awareness (Fulton, 2018). Practicing them enables a person to witness his/her own sensations, emotions and thoughts without judgment, which can help to acknowledge and accept as it is across daily life (Grecucci, Pappaianni, Siugzdaite, Theuninck, & Job, 2015), gaining awareness and insight toward the relief of suffering and greater happiness (Schmidt, 2004), yet with openness, curiosity, and awareness (Fulton, 2018).…”
mentioning
confidence: 99%
“…Research continues to support effectiveness of activities and programs broadly connected to mindfulness and meditation exercise. Practicing them enables a person to witness his/her own sensations, emotions and thoughts without judgment, which can help to acknowledge and accept as it is across daily life (Grecucci, Pappaianni, Siugzdaite, Theuninck, & Job, 2015), gaining awareness and insight toward the relief of suffering and greater happiness (Schmidt, 2004), yet with openness, curiosity, and awareness (Fulton, 2018).…”
mentioning
confidence: 99%